Performative Identities in Culture : From Literature to Social Media - Jaworska-Biskup, Katarzyna,; Zawadka, Beata, (Literature and Cultural Studies E-Books Online, Collection 2025., 2024)
This book's primary task is to test the contemporary value of performance and performativity. Performative Identities in Culture: From Literature to Social Media undertakes this task via a host of chapters on a vast spectrum of performativity-related topics such as: literature (British, American, Welsh), film, art, social media, and sports. Within these contexts, the book raises a number of questions relevant today. How is minority culture constructed and performed in literature? How can one manifest identity in multicultural contexts? How has performativity been transformed in audiovisual media, like film, video games and social media? And, can the digital itself be performative?